Pengaruh Peran Orang Tua dan Guru dalam Menumbuhkan Jiwa Wirausaha Siswa SMKS di Jakarta Selatan - Sugeng Haryono; Solikhin Solikhin; Nurlaela Nurlaela (Universitas Indraprasta PGRI Jakarta, 2020)
Vocational High Schools (SMK) is a type of formal school that provides special education, including entrepreneurship education that can lead students to be a graduate who is ready to enter and participate professionally in the business and industrial world. So that in this study there are several objectives, including identifying the influence of the role of parents and teachers in fostering the entrepreneurial spirit of SMKS students in South Jakarta. This research was conducted using a correlational survey method. Meanwhile, the analysis used to test the truth of the hypothesis was carried out by simple linear regression analysis. The population in this study was 50 students of private vocational schools in South Jakarta. Therefore. the sample was obtained by taking 100% of the population. Thus, the sample size was 50 students of private vocational schools in South Jakarta. The results showed that there was an influence of the Role of Parents together with the Role of Teachers on Fostering the Entrepreneurial Spirit of Students in South Jakarta Vocational High School. This was confirmed by the value of the hypothesis calculation obtained that the value of Sig = 0.000 <0.05 and Fcount = 41.488> Ftable = then H0 was rejected, which meant that the regression coefficient was significant.